The Kinds of Personality Disorders of The Main Character in Inside Out Movie Script - Firman Nur Zaman; Udayani Permanaludin (Universitas Islam Negeri Sunan Gunung Djati, 2020)
Movie script is a narrative literary wok that has intrinsic elements in it, that the intrinsic elements are theme, setting, point of view, plot, moral value, and last but not least are character and characterization. Movie script that are visualized into movies are categorized as modern dramas. Nowdays, the movie is used as a medium of entertainment and as a medium for delivering messages. This research aims to find two things, that is the personality disorders experienced by the main character in “Inside Out” movie script by Pete Docter. In this research, the researcher uses Sigmun Freud’s psychoanalytic theory (1923), and assisted by other supporting theories. The result of the research found that there were eight types of personality disorders of ten types of personality disorders. This research uses DSM-V (2013) as a reference for discussion of personality disorders.Keywords: Personality Disorder, Main Character, Inside Out Movie, Riley, Author, Dialogue, Narration.